The Relationship Between Personal Hygiene And The Identification Of Soil Transmitted Helminths (STH) In Brick Craftsmen In Ngreco Village, Kandat District, Kediri Regency - Dwi Haryatmi (Universitas Widya Gama Mahakam Samarinda, 2023)
Background : Helminthiasis is an infectious disease caused by parasitic worms that enter the human body. Helminthiasis can affect the health condition, nutrition, intelligence, and productivity of individuals, thus reducing the quality of human resources. One of the causes of helminth infection is soil-transmitted helminths (STH), including Ascaris lumbricoides, Trichuris trichiura, and Hookworm, which are transmitted through the soil. Occupations related to soil can increase the frequency of helminth infections, and one such profession is brickmakers. Poor personal hygiene can facilitate the transmission of STH worm infections. Objectives : The objective of this study is to determine or analyze the infection of STH worm eggs and the relationship between personal hygiene and STH worm egg infection among brickmakers in Ngreco Village, Kandat District, Kediri Regency. Research Methods : This study utilizes a descriptive analytical approach with a cross-sectional design. The total sampling technique was employed to obtain 33 fecal samples from brickmakers. Data collection was conducted through questionnaire administration. The data were analyzed using univariate and bivariate analysis (chi-square). Results : The findings of the study indicate that among individuals with poor personal hygiene, 2 samples were found to contain STH worm eggs, specifically Ascaris lumbricoides, with a percentage of 6%. On the other hand, among individuals with good personal hygiene, no STH worm eggs were found, with a percentage of 0%. The chi-square test yielded a result of p=0.002 (p<0.05), indicating a significant relationship. Conclusion : There is a relationship between personal hygiene and STH infection among brickmakers in Ngreco Village, Kandat District, Kediri Regency.